The Philosophy of External Public Debt Management - Matevosyan, Ashot; Grigoryan, Ani (Տիգրան Մեծ)
The main goal of the presented article is to propose effective solutions in the philosophical context of the management of the foreign public debt of RA. The Government of the RA should adopt as a priority the philosophy of attracting borrowed funds from the domestic market.Considering also the fact that the Republic of Armenia re-lied on the philosophy of ensuring doubledigit economic growth, having a long-term goal to increase the real GDP indicator, which will ultimately contribute to reducing the volume of debt obligations. As a priority contributing to this goal, the RA Government intends to significantly increase the volume of trade turnover1, especially in connection with the current geopolitical situation, when Armenia, in particular, is the “gateway of Europe” for Russia, which is the main trad-ing partner.
Keywords: Social philosophy